2005
DOI: 10.1186/1471-2407-5-70
|View full text |Cite
|
Sign up to set email alerts
|

Familial breast cancer: characteristics and outcome of BRCA 1–2 positive and negative cases

Abstract: Background: The clinical and pathological characteristics and the clinical course of patients with breast cancer and BRCA 1-2 mutation are poorly known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 13 publications
11
46
1
4
Order By: Relevance
“…This is consistent with findings from other populations, indicating that the frequency of BRCA1 mutations is higher in early-onset breast cancer (25)(26)(27). According to Veronesi et al (28), higher histological grade and lymph node invasion were significantly more frequent in patients with high genetic risk. Moreover, we also found that patients with higher risk mutation proved to be significantly associated with the presence of vascular peri- ONCOLOGY REPORTS 23: 1641-1645, 2010 Table II.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with findings from other populations, indicating that the frequency of BRCA1 mutations is higher in early-onset breast cancer (25)(26)(27). According to Veronesi et al (28), higher histological grade and lymph node invasion were significantly more frequent in patients with high genetic risk. Moreover, we also found that patients with higher risk mutation proved to be significantly associated with the presence of vascular peri- ONCOLOGY REPORTS 23: 1641-1645, 2010 Table II.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, we selected 17 articles for this systematic review. Among these seventeen articles, some were excluded for the following reasons: number of events, censored or survival rate at 5 and 10 year could not be distinguished whether it is event or loss for five articles [6,[8][9][10][11]; one used a specific population who had been treated with breast-conserving surgery and radiotherapy [12]. Finally, 11 articles were included in the meta-analyses.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Studies with small sample size conducted in South India, Italy, and France during that time have been summarized in Table 2 [35][36][37].…”
Section: Introductionmentioning
confidence: 99%